Students’ and teachers’ understanding of the WebCas questionnaire for assessing healthrelated behaviors - Rosimeide Legnani; Edina Camargo; Elto Legnani; Eliane Bacil; Nicolau Malta Neto; Wagner Campos (Revista Brasileira de Atividade Física e Saúde)
The objective of this study was to verify students’ and teachers’ understanding of the WebCas questionnaire, which aims to assess health-related behaviors. This cross-sectional, descriptive and exploratory survey used the qualitative technique of focus groups with 24 students and 6 teachers. The students highlighted the need to include colorful drawings, to display the segmentation of the day on the computer screen, to provide small explanatory texts in the questionnaire, and to replace terms that are unusual for children. Teachers suggested the inclusion of two images, one representing the male sex and the other representing the female one, and the creation of a scale to represent the intensities of activities, such as the sensation of tiredness, represented by sweat on the skin and hair and reddened skin. This study presented important contributions provided by students and teachers that enabled a better understanding of the WebCas electronic questionnaire in its application with children and adolescents.